Balancing beauty and science: a review of facial implant materials in craniofacial surgery - Kauke-Navarro, Martin; Knoedler, Leonard; Knoedler, Samuel; Deniz, Can; Stucki, Lars; Safi, Ali-Farid (Frontiers in Surgery, 2024)
Facial reconstruction and augmentation, integral in facial plastic surgery, address defects related to trauma, tumors infections, and congenital skeletal deficiencies. Aesthetic considerations, including age-related facial changes, involve volume loss and diminished projection, often associated with predictable changes in the facial skeleton. Autologous, allogeneic, and alloplastic implants are used to address these concerns. Autologous materials such as bone, cartilage, and fat, while longstanding options, have limitations, including unpredictability and resorption rates.Alloplastic materials, including metals, polymers, and ceramics, offer alternatives.Metals like titanium are biocompatible and used primarily in fracture fixation. Polymers, such as silicone and polyethylene, are widely used, with silicone presenting migration, bony resorption, and visibility issues. Polyethylene, particularly porous polyethylene (MedPor), was reported to have one of the lowest infection rates while it becomes incorporated into the host. Polyether-etherketone (PEEK) exhibits mechanical strength and compatibility with imaging modalities, with custom PEEK implants providing stable results. Acrylic materials, like poly-methylmethacrylate (PMMA), offer strength and is thus mostly used in the case of cranioplasty.Bioceramics, notably hydroxyapatite (HaP), offer osteoconductive and inductive properties, and HaP granules demonstrate stable volume retention in facial aesthetic augmentation. Combining HaP with other materials, such as PLA, may enhance mechanical stability. 3D bioprinting with HaP-based bioinks presents a promising avenue for customizable and biocompatible implants.In conclusion, various materials have been used for craniofacial augmentation, but none have definitively demonstrated superiority. Larger randomized controlled trials are essential to evaluate short-and long-term complications comprehensively, potentially revolutionizing facial balancing surgery.